ZC Model: A Way to Rethink Education in Times of Pandemic (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2021)
The pandemic has brought significant changes to the educational system; therefore, it is necessary to analyze the ZC model as a way to rethink education in times of pandemic. Since the Covid-19 pandemic began, it has brought transformations, specifically in the educational system. As final considerations, the Holistic Pedagogical Model ZC, proposed by Zain Cuadros, shows that the student is not limited only to the classroom or the institution, but is projected to all the actors who intervene as mediators in their development. The interactions that they develop in their contexts should foster the praxis of the knowledge constructed through critical reflection and research.